Did You Hear the One About the Doctor? An Examination of Doctor Jokes Posted on Facebook - Davis, Matthew A; Haney, Carol Sue; Weeks, William B; Sirovich, Brenda E; Anthony, Denise L (JMIR Publications, 2014)
BackgroundSocial networking sites such as Facebook have become immensely popular in recent years and present a unique opportunity for researchers to eavesdrop on the collective conversation of current societal issues. ObjectiveWe sought to explore doctor-related humor by examining doctor jokes posted on Facebook. MethodsWe performed a cross-sectional study of 33,326 monitored Facebook users, 263 (0.79%) of whom posted a joke that referenced doctors on their Facebook wall during a 6-month observation period (December 15, 2010 to June 16, 2011). We compared characteristics of so-called jokers to nonjokers and identified the characteristics of jokes that predicted joke success measured by having elicited at least one electronic laugh (eg, an LOL or "laughing out loud") as well as the total number of Facebook "likes" the joke received. ResultsJokers told 156 unique doctor jokes and were the same age as nonjokers but had larger social networks (median Facebook friends 227 vs 132, P<.001) and were more likely to be divorced, separated, or widowed (P<.01). In 39.7% (62/156) of unique jokes, the joke was at the expense of doctors. Jokes at the expense of doctors compared to jokes not at the expense of doctors tended to be more successful in eliciting an electronic laugh (46.5% vs 37.3%), although the association was statistically insignificant. In our adjusted models, jokes that were based on current events received considerably more Facebook likes (rate ratio [RR] 2.36, 95% CI 0.97-5.74). ConclusionsThis study provides insight into the use of social networking sites for research pertaining to health and medicine, including the world of doctor-related humor.